Alkylation of Ethylbenzene with Cyclohexylchloride: A Statistical Study - Saha, Manoranjan; Chakravarty, Prashanta; Saha, Dipti; Alam, Md Zahangir; Tareque, Mahmud Hasan; Alam, Md Ashraful; Rana, Ashequl Alam (Dhaka University Journal of Science, 2012)
A mathematical model was developed for the alkylation of ethylbenzene with cyclohexyl chloride in the presence of anhydrous aluminium chloride as a catalyst using the Yates Pattern experimental design. The variables chosen for the study were temperature, molar ratio of ethylbenzene to cyclohexyl choloride and amount of anhydrous aluminium chloride. The critical response was the yield of cyclohexylethylbenzene. Main effects as well as interaction effect of molar ratio of ethylbenzene to cyclohexyl chloride and amount of catalyst were statistically significant. The adequacy of the suggested model was checked. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10340 Dhaka Univ. J. Sci. 60(1): 71-76 2012 (January)